Perbandingan Metode Tradisional dan Metode Activity Based Costing dalam Menentukan Harga Sewa Kamar Hotel (Studi Kasus Pada Hotel Madani Syariah Medan) - Fachreza, Mhd Farhan; Ridwan, M.; Kusmilawaty, Kusmilawaty (Journal of Student Development Informatics Management (JoSDIM), 2023)
This study aims to determine whether there are differences in the results of room rental calculations using traditional methods and activity-based costing. This study uses a qualitative method with a comparative study, the type and source of data used is primary data and secondary data which is cost data for 2021. The results of this study indicate that there are differences in the results of calculations using the traditional method and the activity-based costing method, where the results calculations using activity-based costing are cheaper than the results of calculations using traditional methods.